2020
DOI: 10.31234/osf.io/vx34e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Roots of Racial Categorization

Abstract: I examine the origins of ordinary racial thinking. I begin with the belief that visible features are diagnostic of race. I argue that the mechanisms responsible for face recognition have an important, albeit delimited, role to play in sustaining this belief. I then address essentialist conceptions of race. I argue that they are forged, in large part, by the mechanisms responsible for what social psychologists call “entitativity perception.” In defending this approach, I argue against the thesis, defended by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…There is also evidence that applications of the folk concept GROUP are guided by attributions of shared intentionality. A number of studies have found that entitativity perception – the tendency to regard some aggregates of people as more “groupish” than others – is mediated by judgments concerning shared intentionality (for some recent discussions, see Phillips, 2021a, b). For example, people's impression that an aggregate of individuals constitutes a genuine group is enhanced when they observe these individuals moving in synchrony (Ip, Chiu, & Wan, 2006; Lakens & Stel, 2011; Wilson & Gos, 2019).…”
mentioning
confidence: 99%
“…There is also evidence that applications of the folk concept GROUP are guided by attributions of shared intentionality. A number of studies have found that entitativity perception – the tendency to regard some aggregates of people as more “groupish” than others – is mediated by judgments concerning shared intentionality (for some recent discussions, see Phillips, 2021a, b). For example, people's impression that an aggregate of individuals constitutes a genuine group is enhanced when they observe these individuals moving in synchrony (Ip, Chiu, & Wan, 2006; Lakens & Stel, 2011; Wilson & Gos, 2019).…”
mentioning
confidence: 99%